2022
DOI: 10.1164/rccm.202111-2655le
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Clinical Trial Using CoronaVac or BNT162b2 Vaccine as a Third Dose in Adults Vaccinated with Two Doses of CoronaVac

Abstract: Some of the results of these studies have been previously reported in the form of a preprint (medRxiv, [03 November 2021]

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
31
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 8 publications
3
31
1
Order By: Relevance
“…Almost one-third of participants had underlying medical conditions (Table 1). In our separate initial investigation which included sera from individuals with various intervals (51-234 days) between second and third dose [11] and some of whom were selected for third dose vaccination due to low (<60%) post-second dose serum surrogate neutralizing antibodies [25],…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost one-third of participants had underlying medical conditions (Table 1). In our separate initial investigation which included sera from individuals with various intervals (51-234 days) between second and third dose [11] and some of whom were selected for third dose vaccination due to low (<60%) post-second dose serum surrogate neutralizing antibodies [25],…”
Section: Discussionmentioning
confidence: 99%
“…Almost one-third of participants had underlying medical conditions (Table 1). In our separate initial investigation which included sera from individuals with various intervals (51-234 days) between second and third dose [11] and some of whom were selected for third dose vaccination due to low (<60%) post-second dose serum surrogate neutralizing antibodies [25], we showed that administering BNT162b2 about 3 months after two doses of CoronaVac reported a GMT of 59 against Omicron compared to 305 against the ancestral virus after the boost [11]. Costa Clemens et al showed that heterologous boosting with third dose of mRNA or adenoviral vectored vaccines induced greater rise in neutralising antibodies against both Omicron and Delta variants than homologous boosting with inactivated vaccines [9].…”
Section: Discussionmentioning
confidence: 99%
“…While both homologous and heterologous booster regimens are immunologically effective, 20 immunogenicity studies reported higher levels of SARS-CoV-2–specific antibodies, including neutralizing antibodies, in heterologous boosting groups. 11 , 21 In a study conducted in Chile, heterologous boosting with BNT162b2 yielded better adjusted vaccine effectiveness (VE) estimates than homologous boosting with CoronaVac for all outcomes under investigation (symptomatic infection, hospitalization, ICU admission, and COVID-19–related deaths). 22 Our study findings were consistent in observing that both regimens were associated with protection against symptomatic SARS-CoV-2 infection and at higher estimates for heterologous boosting among individuals aged 60 years and older.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence on antibody boosting and waning after vaccination is important as it affects the potential timing of subsequent booster vaccine doses. Here, we demonstrate higher levels of antibody to SARS-CoV-2 following two doses of the mRNA vaccine BNT162b2 compared to two doses of the inactivated vaccine CoronaVac [5, 6], and longer durability of responses for BNT162b2 for at least six months following the receipt of a second dose [7, 11]. Our finding of rapid waning of antibody following receipt of CoronaVac echoes previous reports [7, 11] and indicates that a third dose would likely be needed sooner, and indeed in Hong Kong third doses have been recommended at ≥3 months after the second dose of CoronaVac.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we demonstrate higher levels of antibody to SARS-CoV-2 following two doses of the mRNA vaccine BNT162b2 compared to two doses of the inactivated vaccine CoronaVac [5, 6], and longer durability of responses for BNT162b2 for at least six months following the receipt of a second dose [7, 11]. Our finding of rapid waning of antibody following receipt of CoronaVac echoes previous reports [7, 11] and indicates that a third dose would likely be needed sooner, and indeed in Hong Kong third doses have been recommended at ≥3 months after the second dose of CoronaVac. It is important to recognize, however, that protection against severe COVID could be retained even in spite of waning of protection from infection [12].…”
Section: Discussionmentioning
confidence: 99%